1992
DOI: 10.1021/jm00102a004
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolobenzodiazepines and related systems. 2. Synthesis and biological properties of isonoraptazepine derivatives

Abstract: The synthesis of some derivatives and analogues of 12,13,14,14a-tetrahydro-9H,11H-pyrazino-[2,1-c]pyrrolo[1,2- a][1,4]benzodiazepine (isonoraptazepine) is reported. The new derivatives have been subjected to pharmacological tests for evaluation of antidepressant effects. Neurobehavioral assays were also carried out to acquire data on neurotoxicity and sedative action. Isonoraptazepine analogues and derivatives lacked the pharmacological activity of mianserin and aptazepine and showed properties similar to imip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Specifically, based on the AAA theory, a structural descriptor (i.e., an intramolecular distance) was identified that highlighted 3D similarities between isonoraptazepine derivatives and imipramine. 3 With this work, Maurizio became part of the small group of Italian researchers who succeeded in combining molecular modeling with chemical synthesis and pharmacological testing within a medicinal chemistry publication of high scientific relevance. In the same year, the results of studies performed on newly synthesized C-alkylcalix [4]resorcinarenes, aimed at confirming the conformations and the configurations assigned to those compounds on the basis of NMR experiments, were published as a communication.…”
Section: ■ Early Workmentioning
confidence: 99%
“…Specifically, based on the AAA theory, a structural descriptor (i.e., an intramolecular distance) was identified that highlighted 3D similarities between isonoraptazepine derivatives and imipramine. 3 With this work, Maurizio became part of the small group of Italian researchers who succeeded in combining molecular modeling with chemical synthesis and pharmacological testing within a medicinal chemistry publication of high scientific relevance. In the same year, the results of studies performed on newly synthesized C-alkylcalix [4]resorcinarenes, aimed at confirming the conformations and the configurations assigned to those compounds on the basis of NMR experiments, were published as a communication.…”
Section: ■ Early Workmentioning
confidence: 99%
“…The last two synthetic steps described so far from the work of Kamal et al [47,49,50,51,53] and [54,55,56], all involve the reduction of the nitro group of an N -(2-nitrobenzoyl)pyrrolidine-2-carboxaldehyde diethyl thioacetal derivative to the corresponding amino derivative and workup of the reaction mixture without characterizing the product or checking its purity (TLC). The authors however report that the nitro compounds are efficiently reduced to amino compounds and due to potential stability problems they proceed to the next step.…”
Section: Synthesis Of Pyrrolo[14]benzodiazepinesmentioning
confidence: 99%
“…The comparatively small number of publications on the [1,2- a ] and [1,2- d ] isomers is a reflection of the lesser interest in the biology of these compounds. Nevertheless, it is known that pyrrolo[1,2- a ][1,4]benzodiazepines exhibit a wide spectrum of biological effects, such as antinociceptive CNS [41,42], anti-inflammatory [41], analgesic [43] and fungicidal [44] activity, and are potent sedative [41,45,46], anticonvulsant [45,46], myorelaxant [45,47] and psychotropic [43,47] agents.…”
Section: Introductionmentioning
confidence: 99%
“…3 Because mianserin (1), the structure of which is similar to that of aptazepine (2), exhibits significant 'biostereodis-crimination' in organisms, it is likely that aptazepine will also do so. Surprisingly, only syntheses of racemic aptazepine (rac-2), 4,5 some of its structural isomers, 6,7 and their derivatives and analogues have been reported. However, enantiomers of aptazepine derivatives and related compounds have recently been separated by HPLC using saccharide-coated chiral stationary phase.…”
mentioning
confidence: 99%